Detection of the vitalization effect of Tuber mycorrhiza on sessile oak by the recently-innovated FMM chlorophyll fluorometer - Solti, Ádám (Acta Biologica Szegediensis, 2011)
Mycorrhizae enhance the viability of forest trees by the protection against drought and nutrient deficiencies. Here a FluoroMeter Modul (FMM) Chl a fluorometer developed on the Department of Atomic Physics of the Budapest University of Technology and Economics, was used to typify symbiotic relationship between Quercus and Tuber which has economic impact due to its fruiting body. The actual quantum efficiency photosystem II showed strong correlation with low mycorrhizations up to the level of average mycorrhiztion in sessile oak seedling population, which refers to strict host control on mycorrhization. F690/F735 ratio of peak fluorescence, which is known to correlate negatively to leaf chlorophyll content, implicated that the higher mycorrhization caused probably stronger leaf area expansion. Therefore, the presence of Tuber mycorrhiza on Quercus roots enhanced the vitality of oak trees. The portable and relatively low-price FMM fluorometer proved to be an adequate tool for serial in situ vitality measurements.